How to interpret serum creatinine increases during decongestion - Chávez-Íñiguez, Jonathan S.; Ivey-Miranda, Juan B.; De la Vega-Mendez, Frida M.; Borges-Vela, Julian A. (Frontiers in Cardiovascular Medicine, 2023)
During decongestion in acute decompensated heart failure, it is common to observe elevations in serum creatinine values due to vascular congestion, a mechanism that involves increased central venous pressure that has a negative impact on the nephron, promoting greater absorption of water and sodium. For the treatment of this syndrome, it is recommended to use diuretics that generate a high urinary output and natriuresis to decongest the venous system, during this process the serum creatinine values can rise, a phenomenon that may bother some cardiologist and nephrologist, since raise the suspicion of kidney damage that could worsen the prognosis of these patients. It is recommended that increases of up to 0.5 mg/dL from baseline are acceptable, but some patients have higher increases, and we believe that an arbitrary number would be impractical for everyone. These increases in serum creatinine may be related to changes in glomerular hemodynamics and true hypovolemia associated with decongestion, but it is unlikely that they are due to renal parenchymal damage or truly hypoperfusion and may even have a positive connotation if accompanied by an effective decongestion and be associated with a better prognosis in the medium to long term with fewer major cardiovascular and renal events. In this review, we give a comprehensive point of view on the interpretation of creatinine elevation during decongestion in patients with acute decompensated heart failure.